2013
DOI: 10.1002/mc.22016
|View full text |Cite
|
Sign up to set email alerts
|

A sequence variant in the phospholipase C epsilon C2 domain is associated with esophageal carcinoma and esophagitis

Abstract: A single-nucleotide polymorphism (rs2274223: A5780G:His1927Arg) in the phospholipase C epsilon gene (PLCε) was recently identified as a susceptibility locus for esophageal cancer in Chinese subjects. To determine the underlying mechanisms of PLCε and this SNP in esophageal carcinogenesis, we analyzed PLCε genotypes, expression, and their correlation in esophageal cancer cell lines, non-transformed esophageal cells, 58 esophageal squamous cell carcinomas and 10,614 non-cancer subjects from China. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
(32 reference statements)
4
20
0
Order By: Relevance
“…Our results are similar to the report from Shanghai (24), but contrast with studies from the other two groups (25-26). Our observations of reduced PLCE1 expression in GCA and GNCA are also discrepant from other reported studies (7,27).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are similar to the report from Shanghai (24), but contrast with studies from the other two groups (25-26). Our observations of reduced PLCE1 expression in GCA and GNCA are also discrepant from other reported studies (7,27).…”
Section: Discussionsupporting
confidence: 82%
“…In a third study, Wang et al showed increased protein expression in both ESCC and GCA tissues compared to normal tissues (n=94 for ESCC, and n=13 for GCA)(7). This same group also recently reported that PLCE1 mRNA was significantly higher in ESCC tumors than in matched normal tissues (n=26)(26). In all of the above-mentioned studies, mRNA was assayed by real-time RT-PCR, while protein was assayed by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Two studies demonstrated that the PLCE1 rs2274223 SNP was associated with the risk of ESCC (3,10). Subsequently, Wang et al investigated the PLCE1 protein expression of ESCC tissues with different genotypes of rs2274223 SNP and found a higher expression level in ESCC tissues with the A/G genotype compared with those with the A/A genotype (28). Similar results were observed in the study by Hu et al (10).…”
Section: Discussionsupporting
confidence: 58%
“…Hu et al (10) and Li et al (24) reported decreased mRNA in ESCC tumors compared with that in the adjacent normal esophagus, but no difference in protein expression. By contrast, ESCC tissues exhibited a higher PLCE1 protein expression compared with normal tissues in other studies (3,23,(28)(29)(30). This disparity may be attributed to differences in sample size, genetic background or experimental methods.…”
Section: Discussionmentioning
confidence: 70%